Association of household cleaning agents and disinfectants with asthma in young German adults. Issue 9 (8th May 2017) - Weinmann, Tobias; Gerlich, Jessica; Heinrich, Sabine; Nowak, Dennis; Mutius, Erika von; Vogelberg, Christian; Genuneit, Jon; Lanzinger, Stefanie; Al-Khadra, Saba; Lohse, Tina; Motoc, Irina; Walter, Viola; et al.
Abstract : Objectives: We scrutinised the association of private use of household sprays and disinfectants with asthma incidence in young adults in the transition from school to working life. Methods: Between 2007 and 2009, 2051 young adults aged 19–24 years living in two major German cities took part in the Study on Occupational Allergy Risks II. Self-reported exposure to household sprays and disinfectants was characterised according to a composite score for frequency of use as no use (score=0), low use (score between 1 and the median), medium use (score between the median and the 90th percentile) and high use (score above the 90th percentile). Two outcome variables (current asthma and current wheezing) with four mutually exclusive categories (never, incident, persistent and remittent) were used for the risk analyses. Multinomial logistic regression models examined the association between the frequency of using household sprays and disinfectants with asthma and wheezing adjusting for potential confounders. Results: Compared with no use, high use of disinfectants was associated with a more than twofold increased odds of incident asthma (OR 2.79, 95% CI 1.14 to 6.83). In addition, low/medium use of disinfectants was associated with remittent asthma (OR 2.39, 95% CI 1.29 to 4.47). The evidence for an association between high usage of household sprays and asthma incidence was weak (OR 2.79, 95% CI 0.84 to 9.20). Conclusion: Our results support the hypothesis of an association between the use of cleaning products and elevated risks for asthma and wheezing in young adults at the start of working life.